Barbados : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper summarizes recent development in Barbados's International Business and Financial Services (IBFS) sector and assesses the extent to which the loss of correspondent banking relationships (CBRs) pose a risk to its future. The contribution of the IBFS sector to the local economy has been relatively stable in recent years but its contribution to fiscal revenues has declined. The sector has displayed lower profitability since the global financial crisis. More recently, it suffered from two changes in Canadian tax legislation. Consequently, tax revenues have declined while other expenditures have largely offset such decline. The sector also faces some risks from the loss of CBRs that has affected most Caribbean countries.